Pemberdayaan Bidan Desa Dengan Model Promosi Kesehatan Gadhies Untuk Pencegahan Stunting Di Wilayah Kerja Puskesmas Langsa Lama Kota Langsa - Malinda, Risnati; Irawan, Dedi; Thahura, Farahdiba; Febriyana, Dinda; Syuhada, Amelia (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Introduction: Conditions in Indonesia based on data from the 2019 Nutrition Status Study of Toddlers in Indonesia (SSGBI) are still relatively high, where the prevalence of stunting is 27.67%. The GADHIES model aims to clarify and facilitate work steps in carrying out health promotion and can complement the shortcomings of each of these models. The purpose of this service is to improve the competence of village midwives in health promotion by empowering the community to use local ingredients in making healthy and nutritious food as an effort to prevent stunting, as well as increase public awareness of the dangers of stunting in children. Method: The implementation of this activity goes through three stages of activities, namely planning, implementation and monitoring evaluation. During the planning, a Focus Group Discussion (FGD) began first between the PKM team, the Puskesmas and village midwives. The implementation of the gadhies model health promotion model training for stunting prevention was carried out for 2 days which was attended by 15 village midwives, with 3 resource persons, lecture methods and interactive discussions using power point media, gadhies model posters, gadhies health promotion pocket books, and also the Gadhies Model Training Module. After carrying out this training activity, the team conducted monitoring and evaluation to see the improvement of midwives' competence on the gadhies model health promotion method. Results: There was a significant increase in midwife's competence in health promotion from 2 (13.3%) during the pretest to 14 (93.3%) during the posttest. There was a significant increase in maternal satisfaction with health promotion services by midwives from 4 (26.7%) to 15 (100%) after midwives received health promotion training on the Gadhies model.